United in Diversity? A Study on the Implementation of Sanctions in the European Union - Giumelli, Francesco (2022)
The implementation of European Union (EU) policies has been investigated for several policy areas, but Decisions made under the Common Foreign and Security Policy (CFSP) have rarely been considered. While many CFSP measures are applicable throughout the EU without the need for further action on the domestic level, some Decisions must be implemented by Council Regulations. These Council Regulations adopted with the intent to implement CFSP Decisions have qualities of Directives, which delegate implementing tasks to member states and require transposition. The aim of this article is to investigate whether restrictive measures imposed by the EU are uniformly implemented across the member states, and, if not, to what extent implementation performance varies. We observe significant differences in implementation performance across member states. The findings of this article are twofold. First, we claim that implementation and compliance studies should involve CFSP decisions more systematically. Second, empirical confirmation is provided of how uneven transposition and application occurs also in CFSP matters. This study is based on empirical work that consisted of desk research and semi-structured interviews with national competent authorities of 21 EU member states taking place between March 2020 and January 2021.